5B.01: LONGITUDINAL AND RADIAL LEFT VENTRICLE SYSTOLIC FUNCTION ASSESSMENT IN HYPERTENSIVE PATIENTS. (June 2015) - Muiesan, M.L.; Salvetti, M.; Paini, A.; Bertacchini, F.; Maruelli, G.; Colonetti, E.; Donini, C.; Germano, R.; Rosei, E. Agabiti
Abstract : Objective: Few data are available on the relationship between left ventricular (LV) circumferential and longitudinal systolic function in hypertensive patients with preserved LV ejection fraction (EF). The aim of this study is to analyze LV circumferential and longitudinal systolic function and their main determinants in a group of hypertensive patients. Design and method: In 1285 hypertensive patients (547 female, mean age 57 ± 13 yrs, 77% treated) a standard echocardiographic examination was performed, to assess LV anatomy and systolic function parameters, including EF, Midwall fractional shortening (MidFS) and MidFS adjusted for endsystolic stress (ESS_MidFS). In addition longitudinal systolic function was evaluated by the measurement of tissue Doppler peak systolic velocity of the mitral annulus (Sm). A reduced systolic function was defined in the presence of ESS_MidFS lower than 89% or Sm lower than 8 cm/sec. Results: A modest but statistically significant relationship between MidFS or ESS_MidFS and Sm (r = 0, 08, p < 0, 001) was observed. MidFS was independently related to age, body mass index (BMI), LV mass index, relative wall thickness (RWT) and hear rate, while the main determinants of Sm were age, heart rate, systolic blood pressure and LV mass index. According to previously defined criteria a reduction of Sm and ESS_MidFS was observed in 47% and 26% of patients, respectively. Conclusions: Longitudinal systolic function is impaired in a high percentage of hypertensive patients with preserved EF and identifies a higher number of patients with impaired systolic function. The determinants of longitudinal and circumferential systolic function are, at least in part, different.